Oliver : the second-largest living thing on Earth - Crute, Josh; Taesoo Kim, John (Salem, MA : Page Street Kids, 2018)
Oliver wishes he were as popular and important as Sherman, the largest giant sequoia tree, until he discovers it is enough to be part of something big.
Keywords: Giant sequoia -- Fiction; Envy -- Fiction; Contentment -- Fiction; Sequoia National Park (Calif.) -- Fiction